The death education needs of patients with advanced cancer: a qualitative research - Shenghuan Yang; Chao Yan; Jing Li; Yinglu Feng; Huizini Hu; Yonghong Li (BMC Palliative Care)
Abstract Background Cancer remains a global health concern, with nearly 20 million new cancer cases and approximately 10 million cancer-related deaths reported in 2020.An increasing number of individuals with advanced-stage cancer are likely to confront the reality of mortality.In China, cancer-related deaths hold the top position among factors contributing to resident mortality, accounting for nearly a quarter of all deaths. Patients with advanced-stage cancer contend with both physical challenges such as pain, physical decline, and functional impairments, as well as psychological issues including death anxiety, fear of death, and feelings of meaninglessness and hopelessness during disease treatment. Death education serves as a method to educate patients on coping with death, alleviating death-related anxieties and fears, and approaching death calmly, thereby facilitating a peaceful end-of-life experience. Currently, there is a dearth of death education content tailored to patients’specific circumstances in China. Consequently, this study aims to explore the content of death education needs among patients with advanced-stage cancer in China. Methods A qualitative research based on phenomenology was used to select 19 patients with advanced cancer from November 2022 to June 2023. Semi-structured interviews were used to interview, and Colaizzi 7-step analysis method was used to organize and analyze the data. Results Six themes were extracted: 1. Death cognition and education; 2. Life review; 3. Ethics of death; 4. End-of-life decision-making; 5. Social support; 6. Disease treatment. Conclusions Patients with advanced-stage cancer face significant distress caused by their illness and the prospect of death. This distress can impact their quality of life and even influence treatment decisions. It’s essential to comprehensively assess the current state and needs of patients, engaging in ongoing interventions tailored to individual patient circumstances. This approach involves implementing targeted death education content and methods. When executing death education, it’s imperative to consider the patient’s knowledge framework and their level of acceptance. Integrating the patient’s disease progression and treatment, as well as addressing their negative emotional states, becomes crucial for enhancing the patient’s overall well-being and quality of life.